2017
DOI: 10.1016/j.arr.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on multimorbidity from definition to intervention: An overview of systematic reviews

Abstract: The increasing challenge of multiple chronic diseases (multimorbidity) requires more evidence-based knowledge and effective practice. In order to better understand the existing evidence on multimorbidity, we performed a systematic review of systematic reviews on multimorbidity with pre-established search strategies and exclusion criteria by searching multiple databases and grey literature. Of 8006 articles found, 53 systematic reviews (including meta-analysis and qualitative research synthesis performed in som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
283
2
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(304 citation statements)
references
References 59 publications
(114 reference statements)
10
283
2
9
Order By: Relevance
“…23 Several factors influence prevalence estimates among studies of multimorbidity, including differing geographic settings, recruitment methods, and data collection methods, and the operational definition of multimorbidity. 9,18,[24][25][26][27] In this study, we found that including risk factors has the largest impact on prevalence estimates. Compared to most diseases and symptoms, risk factors are generally based on objective, rather than subjective, measures; are easy to quantify; and are often collected as part of routine examinations (eg, blood pressure and BMI).…”
Section: Discussionmentioning
confidence: 59%
“…23 Several factors influence prevalence estimates among studies of multimorbidity, including differing geographic settings, recruitment methods, and data collection methods, and the operational definition of multimorbidity. 9,18,[24][25][26][27] In this study, we found that including risk factors has the largest impact on prevalence estimates. Compared to most diseases and symptoms, risk factors are generally based on objective, rather than subjective, measures; are easy to quantify; and are often collected as part of routine examinations (eg, blood pressure and BMI).…”
Section: Discussionmentioning
confidence: 59%
“…Multimorbidity is defined as two or more co-occurring chronic conditions without an index condition [1]. Multimorbidity is common among adults, with a general population prevalence estimated to be between 17.3 5 to 71.8% [2]. Multimorbidity reduces physical and social functioning, increases utilization of healthcare services, and leads to higher personal and social costs [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many older people receiving home care suffer from multimorbidity and disabilities associated with both normal ageing and illness, which increase as life expectancy increases (Kontis et al., ). Multimorbidity is defined in different ways depending on the context (Xu, Mishra, & Jones, ), but a commonly used definition was formulated by the World Health Organization (WHO, ) as “more than one chronic condition at the same time” (p. 26). These are often long‐term health conditions that require complex and ongoing care.…”
Section: Introductionmentioning
confidence: 99%